Technology Solutions to Improve the Efficiency of Resource Sharing Among Law Training Institutions in Vietnam - Nga, Pham Thanh (Transactions on Engineering and Computing Sciences, 2022)
Currently, there are about 100 law training institutions in Vietnam. In 2019, Vietnamese law training institutions established a network. This activity is very necessary to support each other in the process of law training between the law training institutions. In this article, the author will mention and present the problem of technology application and recommend solutions in sharing resource activities between law training institutions in Vietnam for the next period.